Personal innovativeness and attitude as predictors to students’ engagement in a learning management system environment / Muhammad Fadhli Abdul Rahman, Irfan Naufal Umar and Zaridah Abdullah. - Abdul Rahman, Muhammad Fadhli; Umar, Irfan Naufal; Abdullah, Zaridah (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2020)
The aim of this study was to investigate on the issue of personal innovativeness and attitude as two important elements that contribute to high engagement in learning within the learning management system (LMS) environment. A survey related to the topic was conducted among university students in Universiti Sains Malaysia (USM) main campus in Penang. The findings show that attitude is a significant predictor on students’ engagement in LMS environment while personal innovativeness is not a significant predictor. The results indicate that the success in learning in the LMS environment is determined by learners’ attitude. If the learners have positive attitude to learn in the system, they will show high engagement and participation in learning.